The Toxicity Effect of Organophosphate (Diazinon) towards Duodenum Histopathology and The Activity of Superoxide Dismutase (SOD) Serum in Rats (Rattus Norvegicus) - S. Efi Ulansari; Anna Roosdiana; Dyah Ayu Oktavianie A. P. (The Journal of Pure and Applied Chemistry Research, 2018)
Diazinon is an organophosphate insecticide that can inhibit acetyl-cholinesterase competitively and increase the production of Reactive Oxygen Species (ROS). ROS affect the activity of antioxidant enzymes such as superoxide Dismutase (SOD), and simultaneously ROS cause damage to the cells and duodenum tissue. The toxicity effect of diazinon was investigated by measuring the activity of SOD serum and histopathology of the duodenum in rats (Rattus norvegicus). The activities of SOD serum were measured by using spectrophotometry, and histopathology changes of the duodenum were observed by using HE staining. Rats were divided into 4 groups, negative control group (K-), P1, P2, and P3 groups which were administrated with diazinon for 8 weeks orally with a dose of 20 mg/kgBW, 40 mg/kgBW, and 60 mg/kgBW respectively. The results showed that administration of diazinon orally decreased SOD activity significantly and caused damage of duodenal villi such as hyperplasia of epithelial cells, epithelial erosion, fatty degeneration, hyperplasia of Liberkuhn gland cells, and hemorrhage in the lamina propria.